PERANCANGAN SISTEM INFORMASI KELENGKAPAN PENGISIAN RESUME MEDISRAWAT INAP DI RSUD MEURAXA KOTA BANDA ACEH - Yanuar, Yudhi (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2019)
This research aimed for the inpatient medical resume information system design completeness at RSUD Meuraxa Kota Banda Aceh. Writer did the research observation at RSUD Meuraxa Kota Banda Aceh. Method research were used qualitative methode with descriptive approach, Development methode used waterfall development method. From result of this research couducted found problems: checking process of medical resume s was not effective so that completeness system of medical resume s did not run properly, there was a the inpatient medical resume was not complete, there was often implementation has been delayed return inpatient medical record. Therefore, the authors make the design of information system medical resume inpatients Unified Modeling Language (UML) as a design method, using Hypertext Processor (PHP)as a program application and MySQL as database.The suggestions from writer is there should have been the development of medical resume information system design completeness to ease process of the required information, having a sosialization to all health officer about filling medical resume s, need to remind to an officer of the room on must of filling medical resume s